الشيخ والشاه مقارنة أوليَّة في الإرث الفكري لمحمد بن عبد الوهاب وولي الله الدِّهلوي The Sheikh and Shah Preliminary Comparison of the Intellectual Legacy of Muhammad ibn ‘Abd Al-WahhÉb and WalÊ Allah DehlawÊ - إبراهيم, حسن أحمد (Journal of Islam in Asia (E-ISSN 2289-8077), 2016)
الملخّص تحاول هذه الدراسة، التي أحسب أنها الأولى من نوعها، أن تقدم مقارنة تحليلية للإرث الفكري للشيخين محمد عبد الوهاب (1703-1791م) في الجزيرة العربية وشاه ولي الله الدهلوي (1703-1761م) في شبه القارة الهندية في إطار واقعهما البيئي. وتخلص إلى أن لفظ "الوهابية الهندية"، الذي ابتدعه بعض المستشرقين لوصف حركة الإصلاح الإسلامي في الهند، والذي يوحي بأن رائدها الدِّهلوي كان مجرد نسخة مطابقة لمعاصره ابن عبد الوهاب، مصطلح غير دقيق، بل لعله خاطئ كليًّا. وذلك لأن دراسة الإرث الفكري لهذين العملاقين تبين بأنهما أسسا في عصر ما قبل الهجمة الإستعمارية على بلاد المسلمين مدرستين متباينتين من حيث التوجه والمحتوى. الكلمات المفتاحية: محمد عبد الوهاب، شاه ولي الله، الإرث الفكري، التجديد الإسلامي. Abstract This is the first study to provide an analytical comparison of the intellectual legacy of two great scholars Muhammad ibn ‘Abd al-WahhÉb (1703-1791) in the Arabian Peninsula and Shah WalÊ Allah DehlawÊ (1703-1761) in the Indian sub-continent in the context of their respective environments. It concludes that the term “Indian Wahhabism”, which was coined by some Orientalists to describe the movement for Islamic reform in India, suggesting that Sheikh DehlawÊ was just a duplicate of contemporary Ibn ‘Abd al-WahhÉb, is not only inaccurate but completely incorrect. The study of the intellectual legacy of these two luminaries reveals that they both founded, prior to the pre-colonial attack on the Muslim world, two schools different in terms of orientation and content. . Keywords: Muhammad ibn ‘Abd al-WahhÉb, ShÉh WalÊ Allah DehlawÊ, Intellectual Heritage, Islamic Revival.